REPRESENTATIONS OF MODERN STANDARD ARABIC IN THE ANIMATED FILM THE STORY OF MUHAMMAD IBN SIRIN / تمثيل اللغة العربية الفصحى في فيلم الرسوم المتحركة قصة محمد ابن سيرين - Muhammad Zaki Aditya; Harun Al Rasyid (Universitas Islam Negeri Palopo, 2026)
This study aims to analyze the representation of Modern Standard Arabic (Fusha) in the dialogue of the animated film Kisah Muhammad Ibnu Sirin on YouTube, and to identify its linguistic standardness and suitability for children learning Arabic. Using a qualitative descriptive method, the analysis focuses on four linguistic indicators (phonological, morphological, syntactic, and lexical) following the Miles and Huberman model. The findings reveal that Fusha is consistently represented without any colloquial (ammiyah) contamination. Phonologically, the articulation of critical letters such as qaf, tha, dhad, and dha complies with standard norms. Morphologically, verbal and nominal wazn patterns are applied accurately. Syntactically, structured i rab rules are met across various sentence structures (jumlah ismiyyah and fi liyyah), conditional constructions (uslub syarth), and rhetorical structures. Lexically, the vocabulary remains standardized and is reinforced by integrated Quranic verses and hadiths. Childrens comprehension is accommodated through a layered simplification strategy using high frequency vocabulary, short sentence structures, and pattern repetition. This study concludes that this animated film is a linguistically valid representation of Fusha and is highly recommended as a supplementary medium for formal Arabic language instruction.